Lectotypification of three names in Polygonatum (Asparagaceae, Polygonateae) - Choi, Tae-Young; Lee, Soo-Rang (Phytotaxa, 2024)
The genus Polygonatum Miller (1754: without page) consists of perennial herbs, distributed in the temperate Northern hemisphere (POWO 2024). It is well appreciated in East Asia for its wide array of commercial uses and the species diversity (Kim et al. 2014, Floden 2017). Despite the increased recognition of its value as a natural resource, knowledge of the taxonomy and phylogenetic relationship among congeners has been lacking (Floden 2014, Chao & Tseng 2019). There are unresolved nomenclatural problems (Floden & Schilling 2018), in Polygonatum, around 340 binomials for 76 accepted species (IPNI 2024, POWO 2024, WFO 2024) have been published since Miller (1754), hence often the taxonomic identity of the many species is not straightforward and always in the flux.